Localization of outer surface proteins A and B in both the outer membrane and intracellular compartments of Borrelia burgdorferi. - Brusca, J S (1991)
Borrelia burgdorferi B31 with and without outer membranes contained nearly identical amounts of outer surface proteins A and B. The majority of each immunogen also was localized intracellularly by immunocryoultramicrotomy. These results are inconsistent with the widely held belief that outer surface proteins A and B are exclusively outer membrane proteins.